BIBLIOMETRIC ANALYSIS OF ORGANIZATIONAL CHANGE AND ORGANIZATIONAL DEVELOPMENT STUDIES IN TURKEY - Erdogmus, Nihat; Sayin, Zueleyha (Kafkas University IIBF, 2022)
Scientific studies in the field of organizational change and organization development in Turkey began to increase in the 1990s. With the reflection of the changes in the world on working life and organizations, certain changes have also been experienced in organizational change and organization development studies. For this reason, the aim of the study is to reveal the changes and developments in the field of organizational change and organizational development in Turkey. In this context, articles, theses and books in the field of organizational change and organizational development since the 1990s were analyzed bibliometrically. Along with the study, changes and developments in organizational change and organizational development studies in Turkey are discussed periodically. As a result of the bibliometric analysis, it was seen that there were more conceptual studies in the first years, empirical studies increased over time, public institutions were frequently preferred as application areas, and the studies focused on business, public administration and education. Based on these findings, the developments and changes in the field are discussed.
Keywords: Organizational change; organization development; bibliometric analysis; MANAGEMENT; SCIENCE; Business & Economics